IN VITRO EVALUATION OF ANTHELMINTIC ACTIVITY OF ETHANOLIC EXTRACT OF CENTELLA ASIATICA LINN. IN INDIAN ADULT EARTHWORMS - DATTA, SWAGATA; NINGTHOUJAM, GEETANJALI; ZOSANGPUII, CHRISTINA; SHYAMASAKHI, PAONAM; MEENA, NAMEIRAKPAM (International Journal of Current Pharmaceutical Research, 2021)
Objective: Helminthiasis is one of the most prevalent parasitic infestations worldwide posing a major threat to public health. The control of these nematodes has relied largely on the use of a limited number of anthelmintics. However, emerging resistance and side effects to the currently available anthelmintic drugs is a major concern and discovery of newer anthelmintics with a novel mode of action is the need of the hour. The present study is aimed to evaluate the anthelmintic activity of ethanolic extract of Centella asiatica Linn. (EECA) on Indian earthworms (Pheretima posthuma). Methods: The earthworms were divided into 4 groups with 6 worms in each group. The anthelmintic activity of EECA at two different concentrations (25 mg/ml and 50 mg/ml) was evaluated by assessing the time of paralysis and time of death of the worms. Albendazole was used as standard and 2% gum acacia as control. Results: Albendazole at 25 mg/ml showed the highest anthelmintic activity and had significant difference (p<0.001) with EECA at both 25 mg/ml and 50 mg/ml. Conclusion: Both doses of the test drug showed anthelmintic activity but the extract at either dose was found to be less effective than the standard drug. Further studies with higher doses of the extract should be done to evaluate the anthelmintic activity in a dose-dependent manner.